Tragic uprising and new forms of social insurrection - Maffesoli, Michel; Agar Corbinos, Lorenzo (Acta Bioethica, 2002)
Urban areas are experiencing a latent rebellion, which is manifesting itself in numerous forms; each wave the culmination of increasing variety and imagination. Violence, a physical expression of this rebellion captures the hatred felt towards the establishment, in particular towards the prevailing social networks and societal relationships currently in force. It is therefore necessary to reflect upon the unthinkable, over that which we have considered unthinkable since the non-rational: to think that the non-rational is far from being irrational. The spirit of this great social asepsis has sought to expel the darkness, which corrodes both the body of the individual and society as a whole. Analysis, in terms of social contract, citizenship, and a democratic ideal has been incapable of explaining the aforementioned detonation of tribal passion and emotion. The question that we now face is how must we confront this flammable reality within the bounds of normative ethics and morality.